2018
DOI: 10.1515/folmed-2017-0078
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities of COPD in Bulgarian Patients – Prevalence and Association with Severity and Inflammation

Abstract: The present study suggests high prevalence of CVD comorbidities in COPD patients and association with the disease severity. Metabolic syndrome is a common comorbidity and is associated with increased inflammatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Smith et al (22) noted that hyperlipidemia, hypertension and anxiety were the most common comorbidities, while Miyazaki et al found that HT (36%) to be the most prevalent, closely followed by GER (34%) and cardiac diseases (32%) (23). Stratev et al, on the other hand, found that the most common comorbidities were HT (70.4%), heart failure (47.4%), IHD (37.5%) and DM (21.4%) (24). In their study on 739 COPD patients, Koskela et al found that HT (41%) was the most common comorbidity, followed by chronic psychiatric conditions (33%), heart disease (22%) and DM (15%) (3).…”
Section: Discussionmentioning
confidence: 99%
“…Smith et al (22) noted that hyperlipidemia, hypertension and anxiety were the most common comorbidities, while Miyazaki et al found that HT (36%) to be the most prevalent, closely followed by GER (34%) and cardiac diseases (32%) (23). Stratev et al, on the other hand, found that the most common comorbidities were HT (70.4%), heart failure (47.4%), IHD (37.5%) and DM (21.4%) (24). In their study on 739 COPD patients, Koskela et al found that HT (41%) was the most common comorbidity, followed by chronic psychiatric conditions (33%), heart disease (22%) and DM (15%) (3).…”
Section: Discussionmentioning
confidence: 99%
“…Score ranges from 0 to 100, with higher scores indicating more limitations. In this study, the number of exacerbations per patient was compared to SGRQ score for evaluation [8][9][10].…”
Section: Methodsmentioning
confidence: 99%
“…Literature data [2] show that COPD is one of the predominant causes of death [8] with a global prevalence of up to 10.1% with an upward trend in the following decades [2]. It has been proven that COPD leads to significant disability [10] and is now the third leading cause of death in the world [11]. This pathology is a significant medical and social problem due to the high levels of mortality and disability of patients [10], especially due to its comorbidity with other diseases.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven that COPD leads to significant disability [10] and is now the third leading cause of death in the world [11]. This pathology is a significant medical and social problem due to the high levels of mortality and disability of patients [10], especially due to its comorbidity with other diseases. The most common comorbid conditions are cardiovascular pathology, diabetes mellitus, osteoporosis, chronic kidney disease, etc.…”
Section: Introductionmentioning
confidence: 99%